Behavioural recovery following transplantation of substantia nigra in rats subjected to 6-OHDA lesions of the nigrostriatal pathway. II. Bilateral lesions. - Dunnett, S; Björklund, A; Stenevi, U; Iversen, S (1981)
Rats with a unilateral transplant of embryonic substantia nigra, placed in a cortical cavity overlying the caudate-putamen, were compared with control animals on a range of behavioral tests following bilateral 6-OHDA lesions of the ascending dopaminergic nigrostriatal pathway. Tests designed to reveal behavioural asymmetry--such as spontaneous, tail-pinch and amphetamine-induced rotation, sensorimotor orientation, and side preference in a T-maze--revealed that the rats with bilateral 6-OHDA lesions and a unilateral transplant are similar to unilaterally lesioned animals with one intact nigrostriatal pathway. Both transplanted and bilaterally lesioned control rats became spontaneously akinetic after the second 6-OHDA lesion. This akinesia could be reversed by a low dose of amphetamine (0.5 mg/kg) in the transplanted but not in the non-transplanted control rats. The attenuated effects of apomorphine and L-DOPA on activity and rotation suggest that the nigral transplant produced a partial reversal of receptor supersensitivity following the 6-OHDA lesion on the same side as the transplant. However, other effects of the bilateral 6-OHDA lesion, including the development of aphagia, adipsia and akinesia, were not reversed by the presence of the transplant. The transplants were shown by fluorescence histochemistry to have densely reinnervated the dorsal parts of the denervated caudateputamen on the side ipsilateral to the transplant. The results show that intracortical nigral grafts reinnervating parts of the dorsal caudate-putamen can reverse some, but not all, functional impairments associated with bilateral destruction of the nigrostriatal pathway.